Cinnamic acid conjugated with triazole acetamides as anti-Alzheimer and anti-melanogenesis candidates: an in vitro and in silico study - Amir Shervin Shokouhi Asl; Mohammad Hosein Sayahi; Mohammad Hashem Hashempur; Cambyz Irajie; Amir Hossein Alaeddini; Seyedeh Niloufar Ghafouri; Milad Noori; Navid Dastyafteh; Javad Mottaghipisheh; Mehdi Asadi; Bagher Larijani; Mohammad Mahdavi; et al. (Scientific Reports)
Abstract In this study, new cinnamic acid linked to triazole acetamide derivatives was synthesized and evaluated for anti-Alzheimer and anti-melanogenesis activities. The structural elucidation of all analogs was performed using different analytical techniques, including 1H-NMR, 13C-NMR, mass spectrometry, and IR spectroscopy. The synthesized compounds were assessed in vitro for their inhibitory activities against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and tyrosinase enzymes. Among synthesize derivative compound 3-(4-((1-(2-((2,4-dichlorophenyl)amino)-2-oxoethyl)-1H-1,2,3-triazol-4-yl)methoxy)-3-methoxyphenyl)acrylic acid (10j) exhibited the highest activity against BChE with an IC50 value of 11.99 ± 0.53 µM. Derivative 3-(3-methoxy-4-((1-(2-oxo-2-(p-tolylamino)ethyl)-1H-1,2,3-triazol-4-yl)methoxy)phenyl)acrylic acid (10d), bearing a 4-CH3 group, was identified as the most potent AChE inhibitor. In terms of tyrosinase inhibition, 3-(3-methoxy-4-((1-(2-((2-methyl-4-nitrophenyl)amino)-2-oxoethyl)-1H-1,2,3-triazol-4-yl)methoxy)phenyl)acrylic acid (compound 10n), demonstrated 44.87% inhibition at a concentration of 40 µM. Additionally, a kinetic study of compound 10j which 2,4-dichlorophenyl substituents against BChE revealed a mixed-type inhibition pattern. Furthermore, molecular docking and molecular dynamic studies of compound 10j were conducted to thoroughly evaluate its mode of action within the BChE active site.